Treating juvenile idiopathic arthritis to target: recommendations of an international task force. Issue 6 (11th April 2018) - Ravelli, Angelo; Consolaro, Alessandro; Horneff, Gerd; Laxer, Ronald M; Lovell, Daniel J; Wulffraat, Nico M; Akikusa, Jonathan D; Al-Mayouf, Sulaiman M; Antón, Jordi; Avcin, Tadej; Berard, Roberta A; Beresford, Michael W; et al.
Abstract : Recent therapeutic advances in juvenile idiopathic arthritis (JIA) have made remission an achievable goal for most patients. Reaching this target leads to improved outcomes. The objective was to develop recommendations for treating JIA to target. A Steering Committee formulated a set of recommendations based on evidence derived from a systematic literature review. These were subsequently discussed, amended and voted on by an international Task Force of 30 paediatric rheumatologists in a consensus-based, Delphi-like procedure. Although the literature review did not reveal trials that compared a treat-to-target approach with another or no strategy, it provided indirect evidence regarding an optimised approach to therapy that facilitated development of recommendations. The group agreed on six overarching principles and eight recommendations. The main treatment target, which should be based on a shared decision with parents/patients, was defined as remission, with the alternative target of low disease activity. The frequency and timeline of follow-up evaluations to ensure achievement and maintenance of the target depend on JIA category and level of disease activity. Additional recommendations emphasise the importance of ensuring adequate growth and development and avoiding long-term systemic glucocorticoid administration to maintain the target. All items were agreed on by more than 80% of the members of the Task Force. A research agenda was formulated. The Task Force developed recommendations for treating JIA to target, being aware that the evidence is not strong and needs to be expanded by future research. These recommendations can inform various stakeholders about strategies to reach optimal outcomes for JIA.